Implementasi Rukhsah Syar'iyyah dan Kaidah al-Taisīr bagi Penderita Penyakit Inkontinensia Urin - Imran Muhammad Yunus; Abdul Qadir Gassing; Muammar Bakry (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2023)
This study aims to determine the implementation of rukhsah syar'iyyah and the application of al-taysīr rules in urinary incontinence sufferers. This research is a type of qualitative research (library study) with a normative theological and philosophical approach. The results of this study show that, first, rukhsah can be found for urinary incontinence sufferers in several types and applications. Second, urinary incontinence has several types and not all types can get rukhsah, such as total incontinence. Other types can get rukhsah as long as they meet the existing requirements, based on the rules of al-taysīr.